Capillary electrophoresis to approach sorbate usage in processed meat products in Brazil - Mesquita, Estela [UNESP]; Petruci, João F. S. [UNESP]; Cardoso, Arnaldo A. [UNESP]; Monteiro, Magali [UNESP] (Springer Nature, 2018)
Sorbate is a highly used preservative in a wide range of processed foods, including meat products. In this work sorbate usage in commercial processed meat products from the Brazilian market was evaluated. A capillary electrophoresis method for sorbate analysis using ethanol:water extraction solution (1:2, v/v) and sodium tetraborate (20 mmol L−1) electrolyte solution was validated. Low limits of detection (0.4 mg L−1) and quantification (1.0 mg L−1), good precision (RSD = 3.6%) and suitable accuracy (70.2%, RSD = 1.8%) were attained. Linearity was observed from 1.0 to 15.8 mg L−1, with r ≥ 0.999. The proposed method was applied to Brazilian pork and hot dog sausages, salami, ham and mortadella. A peak of sorbate between 4 and 6 min was found in pork and hot dog sausages, poultry and pork mortadella, but not in ham and salami. The sorbate levels ranged from 54.0 to 976.4 mg kg−1. Sorbate concentration exceeded the 200 mg kg−1 limit of the Brazilian legislation in all sorts of products in the majority of the brands despite there being no information regarding sorbate on the label. These results indicated the widespread use of sorbate, turning this into food for thought.
Keywords: Capillary electrophoresis; Preservatives; Processed meat products; Sorbate